Comparison of adverse maternal and perinatal outcomes between induction and expectant management among women with gestational diabetes mellitus at term pregnancy: a systematic review and meta-analysis - Rong Luo; Wendy Wen; Daniel J. Corsi; Deshayne B. Fell; Monica Taljaard; Shi Wu Wen; Mark C. Walker (BMC, 2023)
Abstract Background Induction at 38-40 weeks of gestation has been broadly suggested for women with gestational diabetes mellitus (GDM), yet its benefits and risks remain unclear. This study aimed to systematically review and meta-analyze existing evidence on the effect of induction at term gestation among women with GDM. Methods We searched MEDLINE, EMBASE, Cochrane Libraries, and Web of Science from inception to June 2021. We included randomized controlled trials (RCTs) and observational studies comparing induction with expectant management among GDM term pregnancies. Primary outcomes included caesarean section (CS) and macrosomia. All screening and extraction were conducted independently and in duplicates. Meta-analyses with random-effects models were conducted to generate the pooled odds ratios (ORs) and 95% confidence intervals (CIs) using the Mantel-Haenszel method. Methodological quality was assessed independently by two reviewers using the Cochrane Risk of Bias Tool for RCTs and the Newcastle-Ottawa Scale for observational studies. Results Of the 4,791 citations, 11 studies were included (3 RCTs and 8 observational studies). Compared to expectant management, GDM women with induction had a significantly lower odds for macrosomia (RCTs 0.49 [0.30-0.81]); observational studies 0.64 [0.54-0.77]), but not for CS (RCTs 0.95 [0.64-1.43]); observational studies 1.03 [0.79-1.34]). Induction was associated with a lower odds of severe perineal lacerations in observational studies (0.59 [0.39-0.88]). No significant difference was observed for other maternal or neonatal morbidities, or perinatal mortality between groups. Conclusions For GDM women, induction may reduce the risk of macrosomia and severe perineal lacerations compared to expectant management. Further rigorous studies with large sample sizes are warranted to better inform clinical implications.